Variação na estrutura das comunidades de anfíbios anuros em paisagens antropizadas - Zanetti, Matheus Cezar (2021)
The main objective of community ecology is to investigate the distribution patterns of biodiversity and understand the processes and mechanisms of action of these processes that generate and maintain these patterns. In anthropized environments, communities can be affected in various ways, which makes it necessary to better understand the dynamics of metacommunities in these environments. This work aimed to compare the richness and composition of anuran species in an urban-rural gradient. Tadpoles were sampled in 39 bodies of water, in two reproductive seasons, between September 2017 and March 2018 and between September 2018 and March 2019. Twenty species belonging to five families were recorded. The rural area showed greater species richness and greater beta diversity among local rural communities compared to the urban area. We observed that urban areas harbor less richness and have lower beta diversity than rural areas, with frog species that occur in urban areas being a subset of species that occur in rural areas, where there is a higher turnover of species. Urbanization negatively affects anuran species, so that rural environments show a greater potential for species conservation when compared to the urban environment. We conclude that it is possible to concentrate conservation efforts in urbanized environments and use them in favor of maintaining species diversity through the maintenance of water bodies in urban areas within spaces with patches of vegetation and with a vegetation structure on the margin, within and water body arehers can help population persistence by providing terrestrial habitats for adults and juveniles and aquatic habitats for tadpoles. Likewise, it is suggested that the conservation of water bodies in rural landscapes and the maintenance of heterogeneity within that landscape may be the best way to conserve biodiversity, as well as the development of agro-environmental policies, where it is maintained whenever possible the quality of the environment with a view to increasing and maintaining the biodiversity of anurans.